Modern approaches to digital product development in the conditions of market variability - E. V. Vasilieva; E. A. Morev (Управление)
Currently, the interest in design thinking in the world has made it possible to add many techniques and visual schemes that can solve various kinds of problems, including for building a strategy to achieve the company’s goals, its corporate spirit and the development of creative skills of its employees. Already today, it is possible to call the merit of design thinking the shift of emphasis in corporate goals to customer orientation, to the mobilization of collective intelligence to solve problems, to understanding the importance of empathy, creativity and entrepreneurship. A comparative analysis of existing design thinking frameworks is given, including from researchers of companies and design centers such as Hasso Plattner Institute of Design at Stanford University (d.school), The HPI-Stanford Design Thinking Research Program, Stanford d.school’s Design Thinking framework (IDEO), Google, Intel. Frameworks structure the process of design thinking in 5-6 phases: from empathy, when the needs and requests of consumers are studied, to testing an innovative product or service being created. The place of “design thinking” approach in the general concept of human-centered design is shown. The task of design thinking, the development of innovative products or services focused on human needs, is to provide a solution to a specific problem of a certain target audience. The paper outlines the principles of designing a digital innovative product. The five steps of designing a new product are described and the features of using various visualization techniques are given. The study uses such tools as the “Persona” model, Job Stories and User Stories frameworks. The creating process features of an innovative product based on the integration of design thinking, Lean Startup methodology and the theory of Jobs to Be Done are described. The life cycle of the innovation development “Creation – Evaluation – Training” is presented which is based on the process of validated learning. Changes in the outline of the business model in the lean startup methodology are presented. New segments have been added to the Lean Canvas business model – “Key Partners”, “Key Activities”, “Key Resources”, “Consumer Relations”.